Treatment for Major Depressive Disorder by Repetitive Transcranial Magnetic Stimulation in Different Parameters: A Randomized Double-Blinded Controlled Trial - Zhang, Tingting; Huang, Yueqin; Jin, Yi; Ma, Xiaoyan; Liu, Zhaorui (Frontiers in Psychiatry, 2021)
Background Repetitive Transcranial Magnetic Stimulation (rTMS) has been proven to be safe and effective in treating major depressive disorder (MDD). However, the treatment parameters of rTMS are still divergent and need to be optimized further. The aim of study was to compare the efficacy of rTMS in treating MDD with different parameters of stimulating frequency and location, and course of treatment. Methods Totally 221 patients with MDD were recruited in the randomized, double-blind, controlled trial. All eligible patients were randomly assigned into four treatment groups: (1) 10 Hz in left dorsolateral prefrontal cortex (DLPFC) (n=55), (2) 5 Hz in left DLPFC (n=53), (3) 10 Hz in bilateral DLPFC (n=57), and (4) 5 Hz in bilateral DLPFC (n=56). The patients received treatment for six weeks, and additional 6-week optional treatment. The efficacies were evaluated by Hamilton Depression Rating Scale-24 items (HDRS) and Clinical Global Impressions Scale (CGI). The trial is registered, Chinese Clinical Trial Registry as ChiCTR-TRC-12002248. Results The ANOVAs of HDRS scores up to 6-week and 12-week with repeated measure of time showed a significant effect of duration without statistical difference among four treatment groups, and no significance when time was interacted with inter-group as well. The response rates up until the fifth week were significantly different with the previous week. Conclusions It concludes that there were no statistical differences in the efficacy of rTMS between unilateral left and bilateral DLPFC, and between 5 Hz and 10 Hz for treating MDD.